The modus operandi of transnational computer fraud: a crime script analysis in Vietnam - Van Nguyen, Trong (Trends in organized crime, 2022)
This study aims to better understand transnational computer fraud in Vietnam utilizing crime script analysis. Data from criminal profiles and in-depth interviews with investigators were combined, and the results showed that Vietnam could become an operational base for both domestic and foreign criminals to implement transnational computer fraud. This type of fraud, which includes crimes with only minor technological elements and those involving almost entirely technological factors, represents the intersection of fraud, transnationality, and technology. Technology can support criminals in defrauding victims transnationally without the need for direct interaction. Moreover, the study clarified the different roles of Vietnamese and foreign offenders in the two types of transnational computer fraud: bank card data fraud and phone scams. As the first study of this nature implemented in Vietnam, this research contributes to the knowledge of computer fraud, especially in Asia, providing a foundation for future investigations related to this kind of cybercrime.